The Impact of Menopause on the Mental Health of Women With an Intellectual Disability: A Scoping Review - Corrigan, Stephanie; McCarron, Mary; McCallion, Philip; Burke, Éilish (Journal of applied research in intellectual disabilities, 2025)
ABSTRACT Background Negative mental health implications of menopause found in the general population, combined with high rates of mental health conditions found in women with intellectual disabilities, provide rationale to examine the existing literature to determine the impact of menopause on women with intellectual disabilities. Methods The review was conducted using scoping review methodology by Arksey and O'Malley. A systematic search was conducted across multiple databases. Relevant articles were screened according to inclusion/exclusion criteria. Braun and Clarke's thematic analysis was utilised to identify themes. Results After screening, eight articles satisfied the inclusion/exclusion criteria, and after thematic analysis, themes found were: changes in mood, lack of reporting of psychological symptoms and difficulty attributing psychological symptoms to menopause. Conclusions Findings indicate the paucity of literature and the lack of attention paid to examining the impact of menopause on the experiences and mental health of women with intellectual disabilities.